2009
DOI: 10.1111/j.1525-142x.2009.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

How do changes in parental investment influence development in echinoid echinoderms?

Abstract: Understanding the relationship between egg size, development time, and juvenile size is critical to explaining patterns of life-history evolution in marine invertebrates. Currently there is conflicting information about the effects of changes in egg size on the life histories of echinoid echinoderms. We sought to resolve this conflict by manipulating egg size and food level during the development of two planktotrophic echinoid echinoderms: the green sea urchin, Strongylocentrotus droebachiensis and the sand do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…Egg size is a classic proxy for egg quality. For example, smaller eggs can have reduced lipid content with negative consequences for larval fitness by increasing age at metamorphosis and reducing juvenile quality (Alcorn and Allen 2009;Bertram et al 2009). However, in our study, egg size appeared to be a poor predictor of the further negative impacts observed on settlement success (no effect of adult acclimation and larval culture pCO 2 was observed on egg diameter).…”
Section: Chronic Exposurementioning
confidence: 99%
“…Egg size is a classic proxy for egg quality. For example, smaller eggs can have reduced lipid content with negative consequences for larval fitness by increasing age at metamorphosis and reducing juvenile quality (Alcorn and Allen 2009;Bertram et al 2009). However, in our study, egg size appeared to be a poor predictor of the further negative impacts observed on settlement success (no effect of adult acclimation and larval culture pCO 2 was observed on egg diameter).…”
Section: Chronic Exposurementioning
confidence: 99%
“…In most echinoderms, because of their regulative development, half-, quarter-, and even double-sized eggs can develop normally (McEdward 1996). While these tests seem ideal in some respects, results are not always consistent: larvae from larger eggs develop more rapidly than their half-sized siblings in many studies (Sinervo & McEdward 1988, Levitan 2000, Alcorn & Allen 2009, Allen 2012 but not all (Hart 1995, Emlet & HoeghGuldberg 1997, Allen et al 2006, and larvae from half-sized eggs resulted in smaller juveniles in some species (Hart 1995, Allen et al 2006, Alcorn & Allen 2009, Allen 2012 but not others (Sinervo & McEdward 1988, Allen 2012. Differences among blastomere separation studies may be due in part to the characteristic egg size of a particular species.…”
Section: Effects Of Egg Energy On Larval Growth and Developmentmentioning
confidence: 99%
“…Alcorn & Allen (2009) and Allen (2012) tested for interactions between food level and egg size on size and age at metamorphosis using blastomere separations in 5 species of echinoids, with variable results: 2 species showed significant interactions for both size and age at metamorphosis (Strongylocentrotus droebachiensis and Echinarachnius parma), 1 showed significant interactions for size but not age (Arbacia punctulata), 1 showed significant interactions for age with no data for size (S. purpuratus), and for 1 species, Dendraster excentricus, egg size and food ration did not significantly interact for age or size at metamorphosis. One likely explanation for these differences is that interactions could be masked by species-specific differences in the maternal, genetic, and epigenetic background of regulation of larval development, making it difficult to compare across distantly related taxa if egg energy does not evolve in isolation from other life-history traits.…”
Section: Interactive Effects Of Food and Egg Energy On Development Anmentioning
confidence: 99%
See 2 more Smart Citations